Islamophobic expressions on Facebook : a critical disclosure analysis on discriminatory discourses following terror attacks in San Bernardino, Brussels and Orlando - Naheed Azhari (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research highlights the use of Islamophobic expressions as discriminatory discourses that illustrate the link between discursive constructions of Islamophobia and cultural 'Others' in the Facebook comments. The comments were collected from three international Facebook newspages i.e. Al Jazeera English, BBC News and CNN. The data were the comments made to the news updates surrounding three terror attacks which occurred in San Bernardino, Brussels and Orlando within the year 2015-2016. This study is significant to the current world as it gives insights on how social media such as Facebook is also a place where discriminative ideologies such as Islamophobia is reconstructed and disseminated through the use of language. To critically analyse the data, Discourse-Historical Approach (DHA) as a branch of Critical Discourse Analysis (CDA) was used as the framework focusing on the five chosen topoi (topos of uselessness and disadvantage, topos of danger and threat, topos of burdening and weighting, topos of humanitarianism, and topos of history) as well as the intensification and mitigation strategies. These argumentation strategies from DHA help to understand and explain the intricate complexities of such identity constructions (Wodak 2011a; Wodak et al. 2009). The findings show that the discursive construction of Islamophobia is linked in great extent to Islam and Muslims being associated with negative roles and impacts on global society. This suggests that Islam and Muslims are shown as: (1) a threat to social security; (2) a community with problematic way of life and belief system; and (3) having a negative impact on humanity and global peace. This study also found that the discriminative views upon Islam and Muslims in comments found in Facebook posts were largely overt and explicit. Terms like “Jihadi”, “refugees”, “extremists”, “Arabs” etc. that have negative connotations including the above oppressive arguments and claims were used openly and aggressively to express the Positive-Us and Negative-Them ideologies against Islam and Muslims. Hence, this study reiterates the idea that, from the perspectives of language studies and critical discourse analysis, there is a dire need for all people to foster sensitivity and respect towards other's beliefs and identities possibly through careful selection of words and language use in all realms of communication. This would pave ways to combat the ongoing Islamophobia and anti-Muslim prejudice that have been causing more harm than good.